1999
DOI: 10.1108/eum0000000004564
|View full text |Cite
|
Sign up to set email alerts
|

Predicting behavioural intention in a small business context

Abstract: Investigates the proposition that reasoned action theory can be successfully applied in the small business (dairy farmers) domain. That proposition is supported by the outcome and, in common with many other studies, attitude was found to be the main predictor of behavioural intention. The normative component does not improve the efficacy of the model, possibly because of the routinised nature of the behaviour under scrutiny or the expertise of the decision makers concerned. It seems likely that the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
14
1
2
Order By: Relevance
“…This finding somewhat casts doubt on the results of other studies in TPB, which have neglected the human effect on behaviours (e.g. Thompson & Panayiotopoulos, 1999;Tonglet et al, 2004). Thirdly, this research attempts to provide insights into the relationship between social pressures and cooperative intention.…”
Section: Theoretical Implicationscontrasting
confidence: 43%
“…This finding somewhat casts doubt on the results of other studies in TPB, which have neglected the human effect on behaviours (e.g. Thompson & Panayiotopoulos, 1999;Tonglet et al, 2004). Thirdly, this research attempts to provide insights into the relationship between social pressures and cooperative intention.…”
Section: Theoretical Implicationscontrasting
confidence: 43%
“…It is believed that "attitude toward a certain behavior is determined by a set of salient beliefs about certain outcomes caused by the behaviors and the corresponding evaluation on the outcomes" (Kankanhalli et al, 2005). Because we aim to investigate the personal factors related to the intended behavior of knowledge sharing, the evaluation of outcomes is classified into the costs and benefits that a person expects to experience/receive after sharing knowledge (Thompson, 1999). Moreover, since our research focuses on the Chinese context, we include a number of factors that are important in this context including mianzi (face) and guanxi since factors specific to the Chinese culture are expected to exert an important influence on individual behavior ( Figure 1).…”
Section: Hypothesis Development and Research Modelmentioning
confidence: 99%
“…In the agricultural sector, some studies have shown that 'attitudes' were the most important predictors of behavioural intention (Thompson and Panayiotopoulos, 1999;Garforth et al, 2004;Wolff, 2012). On the other hand, Ellis-Iversen et al (2010) showed that lack of supportive social norms and of self-efficacy deterred farmers from their intention to control some foodborne diseases.…”
Section: Introductionmentioning
confidence: 99%